Consider Carcinoma Cuniculatum in Recurrent Foot Ulcer: A Case Report and Literature Review - Nunes-Abreu, Francisco; Hidalgo-Caro, Ruben; Lorda-Barraguer, Elena; Cristóbal-Redondo, Victor; Céspedes-Guirao, F. Javier (Archives of Plastic Surgery, 2024)
Carcinoma cuniculatum is a variant of squamous cell carcinoma, characterized by a slow growth with progressive crypt-like invasion of deep tissue. This tumor is frequently misdiagnosed as a benign skin lesion both clinically and histopathologically. The final diagnosis is often delayed as it requires a large sample biopsy. We report the case of a 67-year-old patient who presented to us with a recurring chronic ulcer over a surgical scar of 5 years of evolution.Only after a wide resection of the chronic ulcer was it possible to achieve the correct diagnosis of this large and poorly evolving carcinoma. The subsequent reconstruction with a musculocutaneous gracilis free flap allowed the patient to walk again.
Keywords: carcinoma cuniculatum; foot reconstruction; through-and-through defect; gracilis free flap